Teachers' Strategies in Managing the Class - Asrianto Asrianto; Laksmita Rohmayadevi; Umi Rokhayati (Universitas Sulawesi Barat, 2020)
Nowadays the classroom management is very important for the teacher. In Indonesia, the class had several categories. Namely, international class and regular class. The teacher need to be aware of this phenomenon. They should established some strategies in order to manage their class. The population in Indonesian school nowadays was various. There are small and large classes. On this research, the researchers would like to know what kind of strategies that the teacher used in managing the large class. On this research, the researcher used Qualitative approach in the form of Descriptive qualitative design. The result found that there are many strategies that the teacher can use in managing the large class.